Composite fire extinguishing agent for preventing and controlling thermal runaway of high-nickel ternary lithium battery and preparation method of composite fire extinguishing agent
By using a composite fire extinguishing agent composed of perfluoropolyether oil and other components, combined with gas phase flame retardancy, electron neutralization and free radical capture mechanisms, it solves multiple problems of thermal runaway of high-nickel ternary lithium batteries, achieving rapid fire extinguishing and permanent prevention of reignition, which is superior to traditional fire extinguishing agents.
Patent Information
- Application Number
- CN202511282979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2026-01-30
AI Technical Summary
High-nickel ternary lithium batteries pose risks of oxygen release combustion, chain reaction, internal short circuit and reignition when thermal runaway occurs. Traditional fire extinguishing agents cannot effectively suppress internal electrochemical reactions, and water-based fire extinguishing agents are prone to conductivity and have poor permeability.
The composite fire extinguishing agent is composed of components such as perfluoropolyether oil, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, decabromodiphenyl ethane, and poly(4-acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical). It combines gas-phase flame retardancy, electron neutralization, free radical capture, and oxygen-free coverage mechanisms to achieve rapid fire extinguishing and permanent prevention of reignition.
It achieves rapid fire suppression in the event of thermal runaway of high-nickel ternary lithium batteries, ensuring no reignition, and maintains stability and safety under extreme temperatures, which is superior to traditional fire extinguishing agents.
Smart Images

Figure CN121422439A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of new energy battery safety, more particularly, to a composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control and a preparation method thereof. BACKGROUND
[0002] High-nickel ternary lithium battery refers to a ternary lithium battery with high nickel content in the positive electrode material, and is one of the current research and application hotspots in the field of lithium batteries. High-nickel ternary lithium battery has become the mainstream development direction of power battery due to its high energy density, but it has poor thermal stability and the reaction is violent when it thermal runaway, which has the following problems: Oxygen release combustion: high-nickel positive material decomposes and releases a large amount of oxygen, which helps to spread the fire, making the traditional suffocation fire extinguishing method ineffective.
[0003] Chain reaction: a large number of high-activity free radicals (·H, ·OH) are produced by electrolyte combustion, leading to rapid spread of the flame.
[0004] Internal short circuit: thermal runaway leads to internal short circuit, continuously generating heat and free electrons, which is prone to rekindling.
[0005] Rekindling risk: the battery has high temperature and active substances inside, and the traditional fire extinguishing agent cannot continuously cool and isolate oxygen, leading to multiple rekindling.
[0006] The current mainstream clean gas fire extinguishing agents such as perfluorohexanone and heptafluoropropane can only physically suffocate and slightly cool the lithium battery fire, and cannot inhibit the internal electrochemical reaction; the water-based fire extinguishing agent has good cooling effect, but it is easy to conduct electricity and has poor permeability in the battery. Therefore, it is an urgent technical problem in the industry to develop a revolutionary fire extinguishing agent that can multi-dimensionally cooperate, achieve rapid and complete fire extinguishing, and permanently prevent rekindling. SUMMARY
[0007] In view of the deficiencies in the prior art, one of the purposes of the present application is to provide a composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control, which integrates multiple mechanisms such as strong physical cooling, electron neutralization and binding, gas phase chemical flame retardation, permanent free radical capture, and long-acting oxygen isolation, aiming to quickly extinguish high-nickel ternary lithium battery open fire within a few seconds and ensure permanent non-rekindling.
[0008] To solve the above technical problems, the present application provides the following technical solutions: A composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control, comprising the following raw materials by weight percentage: perfluoropolyether oil (PFPE) 35-50%, 1-ethyl-3-methyl imidazole bis-trifluoromethyl sulfonimide salt ([EMIM][TFSI]) 15-25%, decabromodiphenyl ethane (DBDPE) 8-15%, poly(4-acryloxy-2,2,6,6-tetramethylpiperidine-1-oxyl radical) (Poly-TEMPO) 3-8%, carboxylated molybdenum disulfide nanosheet (MoS2-COOH) 1-4%, carboxylated multi-walled carbon nanotube (CNT-COOH) 1-4%, metal nitrate 2-5%, cerium octanoate (C 16 H 31 CeO6) 0.3-1.2%, gallium@boron nitride / polyurethane microcapsule (Ga@BN / PU) 8-15%, hydrophobic silica aerogel nanoparticles 1-4%, surfactant 0.3-1%, hyperdispersant 0.5-2%, antioxidant 0.1-0.5%, benzotriazole (BTA) 0.05-0.3%, low-viscosity dimethyl silicone oil 3-8%; the metal nitrate includes cerium nitrate Ce(NO3)3·6H2O or lanthanum nitrate La(NO3)3·6H2O; the surfactant is sodium perfluoro-nonyloxybenzenesulfonate (OBS); the hyperdispersant is Hypermer KD-6; the antioxidant is Irganox 1010; the low-viscosity dimethyl silicone oil has a viscosity of 50 cSt.
[0009] The functional mechanism of each component is as follows: Perfluoropolyether oil (PFPE): as a chemically inert base solvent, it provides an extremely wide working temperature range (-60℃ to 320℃) and non-flammability. Its high boiling point can cause violent gasification when contacting a fire source, absorbing a large amount of heat and achieving instantaneous cooling.
[0010] 1-ethyl-3-methyl imidazole bis-trifluoromethyl sulfonimide salt ([EMIM][TFSI]): as a co-solvent and ionic conductor, it is miscible with PFPE to form a uniform liquid phase, providing a high ionic conductivity environment and a medium for electron neutralization reactions.
[0011] Decabromodiphenyl ethane (DBDPE): as a gas-phase flame retardant and free radical initiator. It decomposes to release bromine radicals (Br·) at high temperatures, which capture hydrogen radicals and hydroxyl radicals through reactions such as Br·+H·→HBr and HBr+·OH→H2O+Br·, effectively interrupting the combustion chain reaction.
[0012] Poly-TEMPO: As a solid-state permanent free radical scavenger. Its stable nitroxyl radical (·NO) can efficiently quench various free radicals: R·+·NO(Poly)→R-NO(Poly), forming stable products and fundamentally preventing rekindling.
[0013] MoS2-COOH: As a catalytic flame retardant and charring agent. Its two-dimensional sheet structure can promote the formation of a dense and continuous carbon layer on the battery surface, effectively isolating oxygen; at the same time, its lubricity helps the system disperse.
[0014] CNT-COOH: As an electron binding agent. Forming a three-dimensional conductive network inside the battery, providing a directional migration and discharge channel for free electrons generated by short circuits, avoiding local energy accumulation to cause hot spots.
[0015] Ce(NO3)3·6H2O / La(NO3)3·6H2O: As an electron neutralizer. Ce 3+ / La 3+ has variable valence and can directly capture electrons: Ce 3+ +e - →Ce 2+ , inhibiting electrochemical heat generation from the source.
[0016] C 16 H 31 CeO6: As a secondary reaction enhancer. Decomposes at high temperatures to form highly active and dispersed nanometer-sized cerium dioxide (CeO2), which can catalyze the oxidation of toxic gases such as carbon monoxide and further promote the formation of a more dense protective carbon layer.
[0017] Ga@BN / PU: As a long-acting phase change cooling agent. The core metal gallium melts at 29.8°C, absorbing a large amount of latent heat (80 J / g); boron nitride nanosheets prepared by chemical vapor deposition (CVD) enhance polyurethane as wall material, with high thermal conductivity, high strength, and perfect sealing.
[0018] Hydrophobic silica aerogel nanoparticles: As a thermal insulation covering agent. Covered on the surface of the battery, its nanoporous structure provides extreme thermal insulation effect, preventing oxygen diffusion and external heat backflow.
[0019] OBS: As a surfactant. It greatly reduces the surface tension of the system (to about 15 mN / m), significantly improving the spreading and penetration depth of the agent in the complex structure of the battery.
[0020] Hyperdispersant (Hypermer KD-6): as stabilizer. A high molecular graft copolymer compatible with fluorinated systems, prevents nanoparticle sedimentation and agglomeration by steric hindrance, ensuring long-term uniform stability of the system.
[0021] Antioxidant (Irganox 1010): prevents oxidative degradation of the medicament during storage, maintaining the activity of the components.
[0022] Benzotriazole (BTA): as metal passivator. Forms a dense protective film on the metal surface of the injection system, preventing corrosion.
[0023] Low viscosity dimethyl silicone oil: as process aid. Adjusts the overall viscosity, further enhancing permeability and flowability.
[0024] Preferably, the ratio of the raw materials is preferably: perfluoropolyether oil 39.5%, 1-ethyl-3-methyl imidazole bis-trifluoromethanesulfonylimide salt 20%, decabromodiphenyl ethane 10%, poly(4-acryloxy-2,2,6,6-tetramethylpiperidine-1-oxyl radical) 5%, carboxylated molybdenum disulfide nanosheet 2%, carboxylated multi-walled carbon nanotube 1%, metal nitrate 3%, cerium octanoate 0.5%, gallium@boron nitride / polyurethane microcapsule 10%, hydrophobic silica aerogel nanoparticles 2%, surfactant 0.5%, hyperdispersant 1%, antioxidant 0.2%, benzotriazole 0.1%, low viscosity dimethyl silicone oil 5.2%.
[0025] The second object of the present application is to provide a preparation method of the above-mentioned composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control, comprising the following steps: (1) Carboxylate modification of multi-walled carbon nanotubes and molybdenum disulfide nanosheets in a mixed acid solution of concentrated HNO3 and concentrated H2 S O4 at 60℃ for 4h, after the reaction is completed, wash repeatedly with deionized water until neutral, and dry in a vacuum drying oven, and dry for standby; (2) Add perfluoropolyether oil and 1-ethyl-3-methyl imidazole bis-trifluoromethanesulfonylimide salt into a stainless steel reaction kettle with jacket heating and anchor stirring, respectively, turn on the jacket heating to 50±2℃, adjust the anchor stirring speed to 200rpm, and fully dissolve by constant temperature stirring for 30min, then add decabromodiphenyl ethane, low viscosity dimethyl silicone oil and surfactant, increase the stirring speed to 500rpm, and continue stirring for 60min until all components are completely dissolved and dispersed; (3) The pretreated carboxylated multi-walled carbon nanotubes and carboxylated molybdenum disulfide nanosheets are added into the reaction kettle in 4-5 batches, the high-speed shearing emulsifier and the ultrasonic assisted dispersion system are started, the shearing speed is controlled at 10000 rpm, and the treatment is continuously carried out for 60 min. During the process, the temperature is controlled below 40℃ by jacket cooling water. After the treatment is completed, the sample is detected by a laser particle size analyzer to ensure that the dispersion Dv90 is less than 5 μm; (4) The stirring speed is reduced to 400 rpm, and poly(4-acryloyloxy-2,2,6,6-tetramethylpiperidin-1-oxyl radical), metal nitrate and cerium octoate are sequentially added, and stirred and dispersed for 30 min. Then, gallium@boron nitride / polyurethane microcapsules and hydrophobic silica aerogel nanoparticles are added, and stirred at a speed of 400 rpm for 60 min. The addition time of gallium@boron nitride / polyurethane microcapsules and hydrophobic silica aerogel nanoparticles is controlled within 20-30 min. (5) The superdispersant, antioxidant and benzotriazole are added to the mixed system of step (4), the stirring speed is adjusted to 600 rpm, and the stirring is continuously carried out for 30 min. (6) The mixture is transported to a high-pressure homogenizer, and is circulated and homogenized twice at a pressure of 60 MPa. The homogenized material is returned to the reaction kettle, the vacuum system is started, and the defoaming treatment is carried out at a slow stirring speed for 30 min. (7) The defoamed medicament is filtered, the filtrate is filled into a stainless steel barrel, and high-purity nitrogen is filled for protection, and the barrel is sealed and stored.
[0026] Further, in step (1), the volume ratio of concentrated HNO3 to concentrated H2SO4 is 1:3.
[0027] Further, in step (1), the vacuum drying is carried out in a vacuum drying oven at 60℃ for 12 h.
[0028] Further, in step (2), the decabromodiphenyl ethane needs to be pre-crushed and passed through a 200 mesh sieve before being added to the system.
[0029] Further, in step (3), the power of ultrasonic assisted dispersion is 5 kW, and the frequency is 20 kHz.
[0030] Further, in step (3), the molybdenum disulfide nanosheets are dispersed by supercritical CO2 anti-solvent process.
[0031] Further, in step (3), the carboxylated multi-walled carbon nanotubes and carboxylated molybdenum disulfide nanosheets are added into the reaction kettle in 4-5 batches. After each batch is added, the high-speed shearing equipment is operated for 2-3 min before the next batch is added. The total addition time should be controlled within 15-20 min.
[0032] Further, in step (6), the vacuum degree of the vacuum system is -0.095 MPa, and the speed of slow stirring is 100 rpm Compared with the prior art, the present application has the following beneficial effects: 1、The present application selects PFPE / IL as a solvent base, and compounds and customizes nanomaterials (CNT, MoS2), stable free radical capturing agents (Poly-TEMPO), rare earth additives, CVD enhanced microcapsules, etc., to form a composite system with extremely high performance and high stability.
[0033] 2、The present application first deeply integrates the "electron neutralization and binding" mechanism with the traditional "cooling / flame retardant / free radical capture" mechanism, solves the battery thermal runaway problem from the root of energy and material transfer, and realizes real "targeted fire extinguishing".
[0034] 3、The present application successfully solves the technical bottleneck of long-term stable suspension of high solid content and multiple types of nanomaterials in a fluorinated system through strict pretreatment and efficient dispersion and stabilization process. BRIEF DESCRIPTION OF DRAWINGS
[0035] Figure 1 The preparation process flowchart of the composite fire extinguishing agent of the present application; Figure 2 The timing diagram of the multi-mechanism synergistic effect of the fire extinguishing agent of the present application; Figure 3 The fire extinguishing effect comparison curve of the fire extinguishing agent prepared in the embodiment of the present application and perfluorohexanone. DETAILED DESCRIPTION
[0036] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0037] In the following examples, the test materials and reagents, etc. can be obtained from commercial channels unless otherwise specified, and the specific techniques or conditions not mentioned in the examples can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0038] Example 1: Preparation of a composite fire extinguishing agent A for high-nickel ternary lithium battery thermal runaway prevention and control.
[0039] 1、Precisely weigh the following component raw materials: Perfluoropolyether oil (PFPE): 39.5 kg; 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([EMIM][TFSI]): 20 kg; Decabromodiphenyl ethane (DBDPE): 10 kg; Poly(4-acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxy radical) (Poly-TEMPO): 5 kg; Carboxylated molybdenum disulfide nanosheets (MoS2-COOH): 2 kg; Carboxylated multi-walled carbon nanotubes (CNT-COOH): 1 kg; Cerium nitrate / lanthanum nitrate [Ce(NO3)3・6H2O / La(NO3)3・6H2O]: 3 kg; Cerium octanoate (C 16 H 31 CeO6): 0.5 kg; Gallium@boron nitride / polyurethane microcapsules (Ga@BN / PU, d50=15μm): 10kg; Hydrophobic silica aerogel nanoparticles (modified with KH-550): 2kg; Sodium perfluorononenoxybenzenesulfonate (OBS): 0.5 kg; Hyperdispersant (Hypermer KD-6): 1 kg; Antioxidant (Irganox 1010): 0.2 kg; Benzotriazole (BTA): 0.1 kg; Low viscosity dimethyl silicone oil (viscosity 50 cSt): 5.2 kg.
[0040] 2. Preparation method: (1) Multi-walled carbon nanotubes and molybdenum disulfide nanosheets were placed in a mixed acid solution of concentrated HNO3 and concentrated H2SO4 (volume ratio 1:3) and refluxed at 60℃ for 4 h to carry out carboxylation modification. After the reaction was completed, they were repeatedly washed with deionized water until neutral and dried in a vacuum drying oven at 60℃ for 12 h for later use; (2) Add perfluoropolyether oil and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt to a 100L stainless steel reactor equipped with jacket heating and anchor stirring in sequence. Turn on the jacket heating to raise the temperature to 50±2℃, adjust the anchor stirring speed to 200rpm, and stir at a constant temperature for 30min to make them fully miscible. Then add decabromodiphenyl ethane, low viscosity dimethyl silicone oil and surfactant in sequence, increase the stirring speed to 500rpm, and continue stirring for 60min until all components are completely dissolved and dispersed. (3) The pretreated carboxylated multi-walled carbon nanotubes and carboxylated molybdenum disulfide nanosheets are added into the reaction kettle in 4-5 batches (after each batch is added, the next batch is added after the high-speed shearing equipment runs for 2-3 min, and the total addition time should be controlled within 15-20 min), the high-speed shearing emulsifier (10000 rpm) and the ultrasonic auxiliary dispersion system (power 5kW, frequency 20kHz) are started, and the treatment is continued for 60 min, during which the temperature is controlled below 40℃ by jacket cooling water, after the treatment is completed, the sample is detected by laser particle size analyzer to ensure that the dispersion Dv90<5μm; (4) The stirring speed is reduced to 400rpm, and poly(4-acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl radical), metal nitrate and cerium octoate are added in turn, and stirred and dispersed for 30min, then gallium@boron nitride / polyurethane microcapsules and hydrophobic silica aerogel nanoparticles are added, and stirred at a speed of 400rpm for 60min, and the addition time of gallium@boron nitride / polyurethane microcapsules and hydrophobic silica aerogel nanoparticles is controlled within 20-30min; (5) Add superdispersant, antioxidant and benzotriazole to the mixture of step (4), adjust the stirring speed to 600rpm, and continue stirring for 30min; (6) The mixture is transported to a high-pressure homogenizer, and is circulated and homogenized twice at a pressure of 60MPa, and then the homogenized material is returned to the reaction kettle, the vacuum system (vacuum degree-0.095MPa) is started, and slow stirring (stirring speed 100rpm) is carried out for defoaming treatment, which lasts for 30min; (7) Filtration and filling: the defoamed medicament is filtered through a 10μm pore size 316L stainless steel screen filter to remove a small number of possible large particle agglomerates, the filtrate is filled into a 316L stainless steel barrel, and high-purity nitrogen is filled for protection, sealed storage, and the composite fire extinguishing agent A is obtained.
[0041] Example 2: Preparation of fire extinguishing agent B.
[0042] 1. Accurately weigh the following component raw materials: Deionized water: 45kg; Ethylene glycol (antifreeze): 15kg; Decabromodiphenyl ethane (DBDPE): 8kg; Ammonium polyphosphate (APP): 5kg; Tribromomethane (radical trapping agent): 5kg; Cetyltrimethylammonium bromide (CTAB, electron neutralizer): 2kg; Cerium nitrate: 2kg; Commercial paraffin phase change microcapsules (d50=20μm): 8kg; Common hydrophobic white carbon black: 3 kg; Fluorocarbon surfactant (Capstone FS-50): 0.5 kg; Sodium polyacrylate (dispersant): 0.5 kg; Sodium citrate (pH adjuster): 0.5 kg; BHT (antioxidant): 0.2 kg; Benzotriazole (BTA): 0.1 kg; Thickening agent (polyurethane type): 0.2 kg.
[0043] 2. Preparation method: Mix deionized water with ethylene glycol and stir at a speed of 300-500 rpm, then add CTAB, cerium nitrate, sodium citrate, and BTA in sequence and stir to dissolve; add APP and DBDPE, high-speed shear dispersion for 30 min, shear speed 8000-12000 rpm; add tribromomethane, FS-50, BHT, and sodium polyacrylate, stir and disperse for 10-20 min, stirring speed 300-500 rpm; add phase change microcapsules and white carbon black within 15-20 min, stir at a speed of 200-400 rpm for 40 min; add thickening agent to adjust viscosity, homogenize, filter, and obtain fire extinguishing agent B.
[0044] Comparative Example 1: Traditional clean gas extinguishing agent.
[0045] This comparative example uses commercially available pure perfluoroketone (FK-5-1-12) as a comparison.
[0046] Comparative Example 2: Traditional water-based extinguishing agent.
[0047] This comparative example uses a common fine water mist extinguishing agent containing a surfactant (deionized water + 3% KCl + 0.5% FS-50) as a comparison.
[0048] Effect test example: The extinguishing efficiency of the agents A and B obtained in Examples 1 and 2 and Comparative Examples 1 and 2 was tested.
[0049] Test method: 100 Ah NMC811 ternary lithium battery monomer was used, and the needle was used to trigger thermal runaway. After the flame burned stably, a customized spraying system (working pressure 15 MPa, nozzle diameter 50 μm) was used to spray the extinguishing agent at a distance of 20 cm from the battery for 2 s. Thermocouple and thermal imager were used to record the change of battery surface temperature, high-speed camera was used to record the extinguishing time of the flame, and whether the flame reignited within 60 min was observed. The test results are shown in Table 1.
[0050] Table 1 Comparison results of extinguishing efficiency test
[0051] Conclusion: From the test results, the top agent A provided by the main embodiment 1 of the application shows revolutionary performance in all core indicators, and its fire extinguishing speed, cooling effect, anti-reignition ability and environmental adaptability are much better than those of the traditional fire extinguishing agent and the simplified embodiment 2, and the application purpose is perfectly achieved.
[0052] In summary, the composite fire extinguishing agent prepared by the above-mentioned formula and process has the following effects: 1. Extremely fast fire extinguishing speed: The pin prick test on a 100Ah NMC811 battery module shows that the open fire is completely extinguished within 3 seconds after the agent is sprayed, and the maximum temperature on the surface of the battery is reduced from above 800℃ to below 100℃ within 5 seconds.
[0053] 2. Absolute anti-reignition: No reignition occurs within 1 hour, the voltage is always 0V and does not recover, and the temperature is stable below 80℃.
[0054] 3. Free radical is completely removed: Through ESR (electron spin resonance) spectrum test, the concentration of OH free radicals in the gas is reduced by 99.99% within 100ms after spraying.
[0055] 4. Comprehensive environmental adaptability: Good fluidity at-60℃ low temperature, no crystallization freezing; no decomposition and vaporization at 85℃ high temperature, and no decay of fire extinguishing performance.
[0056] 5. Excellent long-term stability: After 30 days of accelerated aging at 70℃ (simulating 1 year of storage), no stratification and no precipitation, the amount of precipitation in centrifugal test is <0.3%, and the decay of fire extinguishing performance is less than 1%.
[0057] 6. Safe and environmentally friendly: The agent itself is not flammable and does not support combustion, and it efficiently suppresses the generation of toxic gases such as HF.
[0058] The application discloses a preferred embodiment, but is not limited thereto, and those skilled in the art can easily understand the spirit of the application according to the above-mentioned embodiments, and make different inferences and changes, as long as they do not deviate from the spirit of the application, they are within the protection scope of the application.
Claims
1. A composite fire extinguishing agent for preventing and controlling thermal runaway of high-nickel ternary lithium batteries, characterized in that, The raw materials include the following weight percentages: perfluoropolyether oil 35-50%, 1-ethyl-3-methylimidazole bis-trifluoromethyl sulfonimide salt 15-25%, decabromobiphenyl ethane 8-15%, poly(4-acryloxy-2,2,6,6-tetramethylpiperidine-1-oxyl radical) 3-8%, carboxylated molybdenum disulfide nanosheet 1-4%, carboxylated multi-walled carbon nanotube 0.5-2.5%, metal nitrate 2-5%, cerium octanoate 0.3-1.2%, gallium@boron nitride / polyurethane microcapsule 8-15%, hydrophobic silica aerogel nanoparticles 1-4%, surfactant 0.3-1%, hyperdispersant 0.5-2%, antioxidant 0.1-0.5%, benzotriazole 0.05-0.3%, low-viscosity dimethyl silicone oil 3-8%; The metal nitrate includes cerium nitrate or lanthanum nitrate; The surfactant is sodium perfluorooctyloxybenzenesulfonate; The hyperdispersant is Hypermer KD-6; The antioxidant is Irganox 1010; The low-viscosity dimethyl silicone oil has a viscosity of 50 cSt.
2. The composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 1, characterized in that, The ratio of the raw materials is preferably: perfluoropolyether oil 39.5%, 1-ethyl-3-methylimidazole bis-trifluoromethyl sulfonimide salt 20%, decabromobiphenyl ethane 10%, poly(4-acryloxy-2,2,6,6-tetramethylpiperidine-1-oxyl radical) 5%, carboxylated molybdenum disulfide nanosheet 2%, carboxylated multi-walled carbon nanotube 1%, metal nitrate 3%, cerium octanoate 0.5%, gallium@boron nitride / polyurethane microcapsule 10%, hydrophobic silica aerogel nanoparticles 2%, surfactant 0.5%, hyperdispersant 1%, antioxidant 0.2%, benzotriazole 0.1%, low-viscosity dimethyl silicone oil 5.2%.
3. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 1 or 2, characterized in that, The method includes the following steps: (1) Carboxylate modification of multi-walled carbon nanotubes and molybdenum disulfide nanosheets is carried out by placing them in a mixed acid solution of concentrated HNO3 and concentrated H2SO4 and refluxing at 60°C for 4h. After the reaction is completed, the mixture is washed repeatedly with deionized water until it is neutral, and then dried in a vacuum drying oven. The dried mixture is reserved for use; (2) Perfluoropolyether oil and 1-ethyl-3-methylimidazole bis-trifluoromethyl sulfonimide salt are sequentially added to a stainless steel reaction kettle with jacket heating and anchor stirring. The jacket heating is turned on to heat to 50±2°C, and the anchor stirring speed is adjusted to 200 rpm. After constant temperature stirring for 30 min, the mixture is fully miscible. Then decabromobiphenyl ethane, low-viscosity dimethyl silicone oil, and surfactant are sequentially added. The stirring speed is increased to 500 rpm, and stirring is continued for 60 min until all components are completely dissolved and dispersed; (3) The pretreated carboxylated multi-walled carbon nanotubes and carboxylated molybdenum disulfide nanosheets are added to the reaction kettle in 4-5 batches. A high-speed shearing emulsifier and an ultrasonic auxiliary dispersion system are started, and the shearing speed is controlled at 10000 rpm. The temperature is controlled below 40°C by jacket cooling water during the process. After 60 min of treatment, the sample is detected by a laser particle size analyzer to ensure that the dispersion Dv90 is less than 5μm. (4) The stirring speed is reduced to 400 rpm, and poly(4-acryloxy-2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical), metal nitrate and cerium octoate are added in sequence, and stirred and dispersed for 30 min, then gallium@boron nitride / polyurethane microcapsules and hydrophobic silica aerogel nanoparticles are added, and stirred at a speed of 400 rpm for 60 min, and the addition time of gallium@boron nitride / polyurethane microcapsules and hydrophobic silica aerogel nanoparticles is controlled within 20-30 min; (5) The superdispersant, antioxidant and benzotriazole are added to the mixed system of step (4), the stirring speed is adjusted to 600 rpm, and the stirring is continued for 30 min; (6) The mixture is transported to a high-pressure homogenizer, and is subjected to cyclic homogenization twice at a pressure of 60 MPa, and then the homogenized material is returned to the reaction kettle, the vacuum system is opened, and slow stirring is performed for defoaming treatment, and the defoaming treatment is continued for 30 min; (7) The defoamed medicament is filtered, the filtrate is filled into a stainless steel barrel, and high-purity nitrogen is filled for protection, and the barrel is sealed and stored.
4. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (1), the volume ratio of concentrated HNO3 to concentrated H2SO4 is 1:
3.
5. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (1), the vacuum drying is performed in a vacuum drying oven at 60°C for 12 h.
6. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (2), the decabromodiphenyl ethane needs to be pre-crushed and passed through a 200-mesh screen before being added to the system.
7. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (3), the power of ultrasonic-assisted dispersion is 5 kW, and the frequency is 20 kHz.
8. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (3), the molybdenum disulfide nanosheet is dispersed by supercritical CO2 antisolvent process.
9. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (3), the carboxylated multi-walled carbon nanotubes and carboxylated molybdenum disulfide nanosheets are added to the reaction kettle in 4-5 batches, and after each batch is added, the next batch is added after the high-speed shearing device runs for 2-3 min, and the total addition time should be controlled within 15-20 min.
10. The preparation method of the composite fire extinguishing agent for high-nickel ternary lithium battery thermal runaway prevention and control according to claim 3, characterized in that: In step (6), the vacuum degree of the vacuum system is -0.095 MPa, and the slow stirring speed is 100 rpm.